Summer precipitation limits plant species richness but not overall productivity in a temperate mesic old‐field meadow. (5th August 2019) - Serafini, John; Grogan, Paul; Aarssen, Lonnie
Abstract: Question: Water availability is a primary regulator of plant productivity and species richness in arid and semi‐arid ecosystems, but its influence in other habitats is much less clear partly because experimental manipulations of water are relatively rare. How important is soil moisture availability relative to other key environmental factors in determining plant species biomass and diversity in temperate mesic grasslands? Location: An old‐field meadow in southeastern Ontario, Canada. Methods: We established a long‐term factorial field experiment to investigate how variation in soil water (achieved by rainout shelters and water additions), nutrients (NPK fertilizer additions), and above‐ground herbivory (deer fence exclosures), interact as regulators of plant production, species richness, and species composition. Above‐ground biomass for each species was determined in replicate plots (1 m 2, n = 10) after five years of treatment applications. Results: The rainout shelters reduced community shoot biomass by 35% relative to ambient (control) plots, with no influence of the fertiliser. To our surprise, however, the fertiliser enhanced community biomass in the ambient and water addition plots to a similar extent. Species richness and Shannon diversity were increased by water addition, but reduced by the rainout shelters and by fertilisation. Total species richness across all replicate plots was 60% higher in the water addition treatment, and almost halved in the water‐reduced treatment. In contrast to the above, the exclosures had negligible impacts on these community variables. Conclusions: Together, these results suggest that in old‐field meadow grasslands: (a) shoot productivity is primarily limited by soil nutrient supply except under drought conditions when water availability becomes the primary constraint; (b) the two main soil resources for plants — water and nutrients — affect productivity and species richness/composition in fundamentally different ways; and (c) future increases in summer soil aridity and anthropogenic nitrogen deposition may interact to reduce vegetation productivity and diversity in temperate mesic ecosystems. Abstract : We investigated the relative importance of variation in soil water (achieved by rainout shelters and water additions), nutrients (NPK fertilization), and above‐ground herbivory (deer fence exclosures), as interactive controls of plant production, species richness, and species composition in a Canadian old‐field meadow grassland. Our results suggest that water and nutrients affect productivity and species richness/composition in fundamentally different ways.